The Efficacy and Safety of Prakash Method of Closed Reduction of Anterior Shoulder Dislocation. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the effectiveness and safety of Prakash method of shoulder reduction in patients of anterior shoulder dislocation presenting to the emergency department.Methods: This cross-sectional study was conducted in the emergency department of Al Qassimi Hospital Sharjah, United Arab Emirates, from 3rd July 2018 to 3rd July 2020. All patients with anterior shoulder dislocation meeting the inclusion criteria were managed using Prakash technique. Outcome was determined in terms of successful reduction and documentation of any technique related complications.Results: A total of 100 patients with mean age 32.5?±?8.3 years were included in this study. Males were 72(72%) and female 28(28%).Majority(96%,n=96) of the shoulders were successfully reduced with Prakash method. No complication related to the technique was noted.Conclusion: Prakash method of shoulder reduction had a high success rate and without any complication. We recommend this procedure as a technique of choice to reduce anterior shoulder dislocations presenting to the emergency department.